Clusters of health behaviours among young adults in Ireland - Anne Nolan; Emer Smyth (The Economic and Social Research Institute (ESRI), 2020)
New ESRI research, funded by HSE Health and Wellbeing, examines how 4 key risk factors for disease (smoking, alcohol consumption, physical activity, diet) cluster together among young adults. Using data from the Growing up in Ireland '98 Cohort at 17 years of age, the research identified 3 distinct health behaviour clusters among young adults in Ireland: a 'healthy' group, an 'unhealthy group' and an 'unhealthy smokers and drinkers group'.
Keywords: 330; Junge Erwachsene; Gesundheitsrisiko; Clusteranalyse; Irland